A novel method of furan determination in beer using gas chromatography with a flame ionization detector - Jana Olšovská; Tomáš Horák; Karel Štěrba (Kvasný průmysl, 2019)
Furan is considered to have a potential carcinogenic effect on human health. Its presence was found in a number of foods including beer. Thus, it is necessary to have a fast and routine method for its determination. This study describes a procedure meeting these requirements using the head-space technique associated with gas chromatography. A capillary column with the length of 60 m, inner diameter of 0.32 mm and the film thickness of 0.25 μm was used for the determination of furan. A flame-ionization detector (FID) was used for the detection. The characteristics of the procedure are presented.